Influence of nitrogen rates with split application on N use efficiency and its eco-economic suitable amount analysis in rice - WANG Mi; YANG Jing-ping; XU Wei; WANG Hua; SUN Jun-hua (浙江大学学报. 农业与生命科学版)
The effect of N fertilizer rates on N use efficiency at different growth stages of rice and its eco-economic suitable N application amount in high-yielding paddy field in Fuyang, northern Zhejiang Province were studied from 2004 to 2005. The nitrogen content of rice leaf, stem, spike, root and in soil was determined at different growth stage of rice under N treatments. The results show that rice yield under different N supply levels increased firstly and dropped as the N rates increase. Compared with the low N applied rate, the higher rate of N input produced no significant effect on rice yield and N use efficiency. However, more N was discharged into environment with higher N application. According to the results of N use efficiency at different growth stages of rice in two years, the proportion of nitrogenous fertilizer input should be adjusted at regreening, tillering and booting stage. According to the rice production and eco-economy benefit analysis, the application amount of N between 195-232 kg·hm-2 could be better for maintaining high rice yield and minimizing N loss in paddy field.